Participation in Leisure and Sports by People with Disability Living in Rural Areas; Vision of Stakeholders in Quebec - Emilie Belley-Ranger; Romain Roult; Hélène Carbonneau; Isabelle Brunet (The Society of Aging and Physical Activity (SAPA), 2016)
People with disability face many constraints that affect their participation in leisure and sports, which can be seen in the gaps in the scientific literature. This study aims to document the specific issues in the leisure and sports participation of people with disability in rural areas. Qualitative research has documented the rurality-related items. Overall, stakeholders (n = 35) working with people with disability in rural areas were met in focus groups (n = 4). Strengths and difficulties have emerged from these testimonials. Being near the community facilitates awareness towards people with disability. However, one of the difficulties refers to the limited number of people with disability in the communities which obstructs the deployment of the leisure and sport offer. The second difficulty is the small number of volunteers and the problem of succession. Finally, availability and dilapidated infrastructure affects the participation in sports and recreation by people with disability in rural areas.